2021
DOI: 10.1093/jjco/hyab064
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study of the efficacy of nivolumab in Japanese patients with advanced melanoma (CREATIVE study)

Abstract: Background Nivolumab, the anti-programmed cell death protein 1 antibody, has been approved for advanced melanoma, mainly based on evidence from Western countries. The profile of melanoma differs between Caucasian and Asian patients. This study was performed to obtain post-marketing data of nivolumab in Japanese patients with advanced melanoma. Methods This prospective, observational study involved patients with unresectable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…While acral and mucosal melanomas reportedly have a noninflamed TME with less efficacy of ICIs, [35][36][37] a Japanese prospective observational study has shown that anti-PD-1 Open access mAb exhibits similar efficacy against these types. 34 We analyzed our cohort according to the type and found that the OS of patients with acral or mucosal melanoma was slightly shorter than that of the others (online supplemental figure S5B), which is consistent with previous studies. [35][36][37] Next, we stained the FFPE samples for CD8 and CD155 before ICI treatment (online supplemental figure S6A).…”
Section: Tigit/cd155 Blockade Overcomes Resistance To Icis In In Vivo Mouse Modelssupporting
confidence: 89%
See 3 more Smart Citations
“…While acral and mucosal melanomas reportedly have a noninflamed TME with less efficacy of ICIs, [35][36][37] a Japanese prospective observational study has shown that anti-PD-1 Open access mAb exhibits similar efficacy against these types. 34 We analyzed our cohort according to the type and found that the OS of patients with acral or mucosal melanoma was slightly shorter than that of the others (online supplemental figure S5B), which is consistent with previous studies. [35][36][37] Next, we stained the FFPE samples for CD8 and CD155 before ICI treatment (online supplemental figure S6A).…”
Section: Tigit/cd155 Blockade Overcomes Resistance To Icis In In Vivo Mouse Modelssupporting
confidence: 89%
“…While acral and mucosal melanomas reportedly have a non-inflamed TME with less efficacy of ICIs, [35][36][37] a Japanese prospective observational study has shown that Open access anti-PD-1 mAb exhibits similar efficacy against types. 34 In our cohort, there was no significant difference in CD8 + T-cell infiltration or CD155 expression among melanoma types. While patients with acral or mucosal melanoma had a slightly shorter OS, multivariate analyses demonstrated that the melanoma type was not a prognostic factor.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“… 2 , 3 , 4 Notably, advanced MCM (unresectable primary or metastatic) is the most common advanced-stage subtype in Japan, accounting for 28%-38% of all melanoma subtypes at this stage. 5 , 6 , 7 MCM is genetically, molecularly, and clinically different from NACM in that it has distinct oncogenic drivers with a 3%-15% infrequent rate of BRAF V600 mutation, 8 a lower tumor mutational burden, 9 and a highly aggressive phenotype with a poorer prognosis. 10 …”
Section: Introductionmentioning
confidence: 99%